4CPS-183 Collaboration with the ophthalmology service in a public residential care home. (March 2019) - de-la-Nogal-Fernandez, MB; Soler-Bartrina, P; Sanchez-Ferreiro, AV; Lopez-Virtanen, BC; Vazquez-Troche, SDC; Valdueza-Beneitez, J; Martinez-Fernandez, V; Noguerol-Cal, M; Casas-Agudo, H; Rodriguez-Maria, M; Mitchell, R
Abstract : Background: Due to the age and clinical situation of the residents in the nursing home, the collaboration with specialists guarantees continuing care. Purpose: Describe the collaboration of the hospital ophthalmology department in resolving queries or consultations concerning the ophthalmological medication used by the residents in the public nursing home of the referential area. Material and methods: A proposal was presented to the ophthalmology service in December 2017. Two doctors collaborated. A transverse study was carried out in January 2018 with residents using eye-drop treatments and their medical records were revised. Data about the use of medication of the S group (ATC codes) was collected between January 2015 and December 2017.The medications which can interact with ophthalmological diseases, e.g. glaucoma and cataracts, were revised, as were the adverse effects of the eye drops. Recommendations and improvement proposals have been sent. Results: In January 2018, of the 194 residents in the care home, 23 were receiving treatment with artificial tears and seven (average age 82.7 years) were being treated, chronically, with eye drops for glaucoma. Of the seven patients, only three were being revised by the specialist. For the four residents without follow-up, the ophthalmologist suggested visiting the residence to measure ocular tension and visual acuity, and later book an outpatient appointment in 2018. Of the seven patients in treatment: one was receiving quadruple therapy (carbonic anhydrase inhibitor, alpha-2adrenergic receptor, beta-blocker and prostaglandin analogues); two received triple therapy; three double therapy; and one received monotherapy (prostaglandinanalogues). A therapeutic of beta-blockers and prostaglandin analogues was detected. The greatest use of ophthalmological preparations (2015–2017) corresponded with lubricants, tobramycin-dexamethasone, tobramycin, diclofenac and latanoprost. Regarding the medication which required to be taken into account with ophthalmological diseases, these were: Anticholinergic drugs which can interact in patients with acute angle–closure glaucoma: hyoscine, tolterodine, tryciclic antidepressant, typical antipsychotic, hydroxycine. Topiramate can produce glaucoma. Alpha–1 adrenergic blockers. The discontinuation (or cancellation or suspension) in cataract interventions needs to be evaluated, due to the risk of inter–operative flaccid iris syndrome. Conclusion: Collaboration with the ophthalmologists was found to be useful and guarantees continuing care and an efficient use of the resources, as well as the acquisition of knowledge. References and/or acknowledgements: Improvement of pharmacological treatments in nursing homes: medication review by consultant pharmacists ejhp.bmj.com/content/22/4/207 No conflict of interest.